Biomechanics of implant fixation in osteoporotic bone - Anderson, Kyle D. (Curr Osteoporos Rep, 2020)
PURPOSE OF REVIEW: The purpose of this review is to critically evaluate the current literature regarding implant fixation in osteoporotic bone. RECENT FINDINGS: Clinical studies have not only demonstrated the growing prevalence of osteoporosis in patients undergoing total joint replacement (TJR) but may also indicate a significant gap in screening and treatment of this co-morbidity. Osteoporosis negatively impacts bone in multiple ways beyond the mere loss of bone mass including, compromising skeletal regenerative capacity, architectural deterioration, and bone matrix quality, all of which could diminish implant fixation. Recent findings in both pre-clinical animal models and in clinical studies indicate encouraging results for the use osteoporosis drugs to promote implant fixation. SUMMARY: Implant fixation in osteoporotic bone presents an increasing clinical challenge that may be benefitted by increased screening and usage of osteoporosis drugs.